THE LANGUAGE AND STYLE OF TOGAY MURAD’S NOVELS - Khidirova R. Munavvara (International Scientific and Current Research Conferences, 2022)
This article discusses the language and style of Togay Murad’s novels. When it comes to the use of saj in prose, issues such as the writer’s creative purpose, skill, and the character of a particular work cannot be ignored. Simplicity of expression is a unique creative principle, the pursuit and achievement of which reflects the high level of prose talent, the richness of the language of the work. T. Murad uses saj not for the purpose of external decoration, silence and high-spirited expression of thought, but for concise, fluent and expressive expression of thought.